Methods and Approaches of College Counselors to Deal with Students’ Psychological Crisis - Guan Ruixia; Zhang Junbo (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The transformation and development of higher education into elite education has led to widespread knowledge and an increase in students' numbers in colleges and universities. Simultaneously, with the increasing diversification of social values and the increasingly fierce social competition, psychological problems caused by college students' study pressure, employment pressure, and personal emotions continue to emerge, and college students have become a group with a high incidence of psychological crises. They also face problems in interpersonal communication as they lack self-psychological adjustment skills and have a low ability to withstand setbacks, resulting in psychological issues. College counselors are university administrators who have the closest contact with students. They have the most direct influence on students. Therefore, in order to urgently bring some kind of psychological crisis intervention, it is important to establish an effective student psychological crisis intervention system and explore the methods and ways of students' psychological crisis intervention. This paper examined counselors' important role in the identification and intervention of college students' psychological turmoil. The study found that the rational application of psychological principles can effectively improve the counselors' working ability in psychological crisis intervention, prevent and reduce the occurrence of college students' psychological crises, and ensure college students' healthy development.